Overview of technical advances that encourage domestic US tar sand development. (2015) - McLendon, Thomas; Soong, Yee; Hedges, Sheila; Jikich, Sinisha; McLendon, William
US domestic tar sand estimated resource exceeds 60 billion barrels (bbl). Production of this resource has been insignificant. Traditional petroleum production methods cannot be applied. Tar sand is highly viscous because over geologic time it was exposed to fluid pathways whereby the light ends could evaporate. The most easily accessible reservoirs are still available. The recent advances in oil/gas production technologies that have made other non-traditional resources capable of development have yet to be applied to tar sand development. Successful tar sand development would also displace some of the considerable imports of asphalt. There are two approaches to US domestic tar sand extraction: mining and subsequent surface processing, and in situ methods. Surface extraction falls into two categories: water or solvent extraction and pyrolytic techniques. In situ extraction attempts have focused on thermal methods [steam flood, electromagnetic radiation (EMR), etc.]. The desired end product determines the extraction method. [Received: December 10, 2013; Accepted: February 20, 2014]